2021
DOI: 10.1371/journal.pone.0258340
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antenatal care, intranatal care and postnatal care utilization: Findings from the 2017 Indonesian Demographic and Health Survey

Abstract: Background and objective Maternal healthcare utilization by young women and adolescent girls is associated with maternal health outcomes and plays a critical role in reducing maternal mortality rates in low- and middle-income countries. This study sought to analyze current data on antenatal care (ANC), intranatal care (INC), and postnatal care (PNC) utilization with a focus on mothers aged 15–24 years in Indonesia. Methods This study was a secondary analysis of data from the 2017 Indonesian Demographic and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
6
11
1
1
Order By: Relevance
“…In terms of pregnancy and postpartum status, we found that more postpartum women had received physical therapy than pregnant women. This finding is in contrast to the previous studies which reported fewer women seeking or utilizing postnatal care than antenatal care [ 37 , 47 ]. It is possible that some pregnant women believe that musculoskeletal discomfort (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In terms of pregnancy and postpartum status, we found that more postpartum women had received physical therapy than pregnant women. This finding is in contrast to the previous studies which reported fewer women seeking or utilizing postnatal care than antenatal care [ 37 , 47 ]. It is possible that some pregnant women believe that musculoskeletal discomfort (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings showed that participant characteristics, such as age, identity and education, were associated with the use of antepartum/postpartum physical therapy, which is in line with the previous studies [ 35 , 36 , 37 ]. However, in contrast to the studies which found that older patients with higher socioeconomic levels [ 27 ] and women with higher education levels [ 26 ] were more likely to use physical therapy, we found that younger participants with lower levels of education were more likely to use physical therapy.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that the respondent’s age had significant association with ANC visits. The result found that older women were more likely to get ANC visits compared to younger women, which is supported by the findings conducted in a low- and middle-income countries [ 48 ]. The reason possibly could be that due to lack of age maturity and information regarding ANC visits, younger women have limitations in their ability to handle and supervise the maternity period, and older women, on the other hand, due to their maturity remain more cautious about pregnancy difficulties [ 49 ].…”
Section: Discussionsupporting
confidence: 71%
“…The explanatory variables were considered as covariates based on their availability in the DHS dataset and extensive literature review [ 4 , 9 , 11 13 , 19 , 21 ]. The explanatory variables for this study were mothers’ place of residence (urban and rural), wealth index (poorest, poorer, middle, richer and richest), mother’s education (no education, primary, secondary and higher), husband/partner’s education (no education, primary, secondary and higher), mother’s age (15–24, 25–34, and 35–49 years), mother’s age at first birth (≤24, 25–34, and 35–49 years), family composition (≤4 and >4 members), number of living children (0–3, 4–6, and ≥7), mother’s working status (no and yes), mother’s healthcare decision-making autonomy (women alone, women and husband/others, and husband/others), and media exposure (no exposure, partial exposure, and full exposure).…”
Section: Methodsmentioning
confidence: 99%